Phase II study of durvalumab (MEDI 4736) plus carboplatin and etoposide in elderly patients with extensive stage small cell lung cancer: Study protocol of turtle study (LOGIK 2003). Issue 1 (15th November 2022) - Ishii, Hidenobu; Azuma, Koichi; Shimose, Takayuki; Yoshioka, Hiroshige; Kurata, Takayasu; Shingu, Naoki; Okamoto, Masaki; Kawashima, Yosuke; Okamoto, Isamu
Abstract: Background: Recently, the addition of antiprogrammed cell death‐ligand 1 (PD‐L1) monoclonal antibodies, including durvalumab and atezolizumab to platinum‐based chemotherapy, has demonstrated clinical benefits in patients with untreated advanced small cell lung cancer (SCLC). However, these clinical trials comprised small populations of elderly patients with SCLC. Therefore, the safety of anti‐PD‐L1 immunotherapy plus platinum and etoposide in elderly patients remains unclear. Methods: This prospective, multicenter, single‐arm study was designed to evaluate the safety and efficacy of durvalumab plus carboplatin and etoposide in untreated elderly patients (aged > 75) with extensive stage (ES) SCLC. A total of 40 patients were recruited. Patients received up to four cycles of durvalumab 1500 mg and carboplatin at a dose equivalent to an area under the curve of 5 on day 1, and etoposide 80 mg/m 2 on days 1 to 3 every 3 weeks as induction treatment, followed by durvalumab maintenance treatment every 4 weeks. The primary endpoint was safety as measured by adverse events according to the Common Terminology Criteria for Adverse Events version 5.0, laboratory analyses, vital signs, and physical examination. Key secondary endpoints were objective response rate, median progression‐free survival, 12‐month overall survival rate, and the completion rate for four cycles of induction chemotherapy. Discussion: The present study was designed to evaluate the safety of durvalumab plus carboplatin and etoposide in elderly patients with ES‐SCLC. Abstract : Recently, the addition of anti‐programmed cell death‐ligand 1 (PD‐L1) monoclonal antibodies, including durvalumab and atezolizumab to platinum‐based chemotherapy, has demonstrated clinical benefits in patients with untreated advanced small cell lung cancer (SCLC). However, these clinical trials comprised small populations of elderly patients with SCLC. Therefore, the present study was designed to evaluate the safety of durvalumab plus carboplatin and etoposide in elderly patients with ES‐SCLC.